Global development finance : the globalization of corporate finance in developing countries. Volume 2, Summary and country tables 2007 (Washington, DC: World Bank, 2007)
The Global development finance is a review of global financial conditions facing developing countries. This volume contains statistical tables on the external debts of the 135 countries that report public or publicly guarantee debt under the Debtor Reporting System (DRS).
lje 16/9/13
Loans
Keywords: Debts, External -- Developing countries -- Statistics; International finance; Investments, Foreign -- Developing countries